Предмет: Математика,
автор: MercyXray
Решите уравнение (x^2+3x+1)(x^2+3x+3)=-1
Ответы
Автор ответа:
0
Решение на фото _______________
Приложения:
Автор ответа:
0
Спасибо огромное!
Автор ответа:
0
(x^2 +3x +1)(x^2 +3x + 3)= -1
x^2 +3x = t
=> (t+1)(t+3) = -1
t^2+4t + 4 = 0
(t+2)^2 = 0
t = -2
=> x^2 +3x = -2
x^2 + 3x +2 = 0
=> x1 = -1
x2 = -2
Я ошибся в комментарии только 2 корня
x^2 +3x = t
=> (t+1)(t+3) = -1
t^2+4t + 4 = 0
(t+2)^2 = 0
t = -2
=> x^2 +3x = -2
x^2 + 3x +2 = 0
=> x1 = -1
x2 = -2
Я ошибся в комментарии только 2 корня
Приложения:
Похожие вопросы
Предмет: География,
автор: Anichka140
Предмет: Химия,
автор: xonap72594
Предмет: Українська мова,
автор: Ign1teFox
Предмет: Литература,
автор: moskalyuk03